ANALISIS INDEKS KEPUASAN PASIEN RAWAT INAP PADA PELAYANAN KESEHATAN DI RUMAH SAKIT BHAYANGKARA KENDARI TAHUN 2021 - Waode Marulana; Nasrul Nasrul; Asrip Putera (Pascasarjana Universitas Halu Oleo, 2021)
This research aims to explore the index of public satisfaction with inpatient services at Bhayangkara Kendari Hospital. This research design uses survey methods with explanatory research approach and data collection is carried out at once in one short study through questionnaires and in-depth interviews. The population in this study was all inpatients at Bhayangkara Kendari Hospital while the study took place. Determination of samples using accidental sampling method, so that the sample size is obtained as many as 100 respondents. The data analysis method used is the Community Satisfaction Index (IKM) referring to Permenpan RI Number 14 at 2017 and Importance-Performance Analysis.The results showed that the inpatient care index at Bhayangkara Kendari was 2.71 with a patient satisfaction index of 67.75 percent so that the overall quality and performance of inpatient services was “B (Good)